Audit of System Information on Accurate Accounting 5 Using COBIT 5 with Domain Monitoring, Evaluate, and Assess (Case Study on ATPIKA Semarang) - Berliana Euniker Rachel Windari; Agnes Advensia Chrismatuti; FX Hendra Prasetya (Soegijapranata Catholic University, 2026)
ATPIKA is a furniture and interior vocational higher education institution in Semarang. In its business activities, especially in recording transactions related to academics, ATPIKA uses accurate Accounting 5 desktop-based applications produced by PT. Cipta Piranti Sejahtera to assist ATPIKA in processing financial data accurately and quickly generating financial statements. Based on interviews with staff and directors, several problems were found. Another fact is ATPIKA has never conducted monitoring and evaluation of the system used. From all the problems that exist in ATPIKA, researchers are motivated to audit using the COBIT 5.0 framework using the MEA domain, which the domain focuses on monitoring, evaluation, and assessment of control. The results of this study after analyzing the level of capability in AEC are at level 3, namely the established process. The conclusion of this study is that ATPIKA has implemented every information technology governance process according to standards, but the understanding of the monitoring and control process on the use of information technology in the staff ranks is still lacking.